EP334 SENTIX – sentinel lymph nodes in patients with cervical cancer: SLN detection and the false negative rate of SLN frozen section (CEEGOG-CX01; ENGOT-CX2; NCT02494063). (1st November 2019) - Kocian, R; Köhler, C; Klat, J; Germanova, A; Plaikner, A; Bajsova, S; Marnitz, S; Ostojich, M; Zapardiel, I; Gil-Ibañez, B; Sehnal, B; Petiz, A; et al.
Abstract : Introduction/Background: SENTIX is a prospective cohort multicenter international study on sentinel lymph node (SLN) biopsy without pelvic lymph node dissection (PLND) in patients with early-stage cervical cancer. SLN frozen section (FS) and pathological ultrastaging were mandatory. Samples from SLN were reviewed centrally for pathological assessment quality control. Only sites experienced in SLN biopsy technique were eligible. Methodology: In total, 47 sites from 18 countries participated in the study. Patients with stages T1a1/LVSI+ - T1b2 (<4 cm or ≤2 cm for fertility sparing), with common tumor types and no suspicious lymph nodes on imaging were pre-registered in the study. Patients remained registered after the surgery if SLN were detected on both sides and if SLN were negative on frozen section. Blue dye, radioactive tracer, indocyanine -green (ICG) or their combinations were all eligible tracers for SLN detection. SLN ultrastaging protocol included a complete processing of all SLN tissue in slices of 2 mm thickness, 2 sections in 150 µm from each block until no tissue left, one stained with H&E and second examined immunohistochemically. Results: Data from 372 patients were analyzed who were pre-registered at the time when the number of cases treated per protocol reached 300. Patient characteristics are shown in table 1. Bilateral detection rate reached 91%. table 2 shows factors influencing SLN detection. Frozen section detected macrometastases (MAC) in 22 cases. SLN ultrastaging found additional 7 cases with MAC, 19 with micrometastases (MIC) and 11 with isolated tumor cells (ITC). Sensitivity of FS was 75.9% for the detection of MAC and 37.3% for any type of SLN involvement. Conclusion: High bilateral detection can be achieved in sites experienced in the SLN biopsy technique. We did not confirm a higher detection rate using ICG. FS failed to detect 26/48 (54%) of cases with MIC or MAC in SLN. Disclosure: This work was supported by a grant from the Czech Research Council (No 16-31643A). Conflict of interest: None of the authors declare a conflict of interest.